Uncovering Fraud in Health Center Capitation Fund Planning - Muhammad Akbar; Prasetyono; Tarjo (Fakultas Ekonomi dan Bisnis, Universitas Udayana bekerjasama dengan Ikatan Sarjana Ekonomi Cabang Bali, 2024)
This study aimed to investigate fraud in capitation fund management at the Pesisir Health Center in Sanjaya Regency. Capitation funds, where healthcare providers are paid a set amount per patient over a specific period regardless of services rendered, are vulnerable to fraud due to inadequate monitoring. Using qualitative methods and a case study approach, data were collected through observations, documentation, and interviews. Findings revealed that fraud motivations included financial pressures to gain more from the funds. Opportunities for fraud arose from monitoring lapses, and rationalizations were made by perpetrators who deemed their actions justified, mirroring widespread similar misconduct. Additionally, those committing fraud typically possessed the necessary skills and experience to manipulate the system effectively